2015
DOI: 10.1088/0957-4484/26/28/284001
|View full text |Cite
|
Sign up to set email alerts
|

Towards instantaneous cellular level bio diagnosis: laser extraction and imaging of biological entities with conserved integrity and activity

Abstract: The prospect for spatial imaging with mass spectroscopy at the level of the cell requires new means of cell extraction to conserve molecular structure. To this aim, we demonstrate a new laser extraction process capable of extracting intact biological entities with conserved biological function. The method is based on the recently developed picosecond infrared laser (PIRL), designed specifically to provide matrix-free extraction by selectively exciting the water vibrational modes under the condition of ultrafas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The soft ablation of tissue by PIRL is achieved under the conditions of desorption by impulsive excitation (DIVE) [21] in which the water molecules contained within the tissue are transferred into the gas phase in an ultrafast, explosive manner. DIVE results in intact cellular biomolecules blasting out of the sample with minimized heating or shock wave damage imposed on the tissue and biomolecules [22] , [23] , [24] , [25] . Kwiatkowski et al showed that the tissue proteome is present in the condensate of the DIVE-induced tissue aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…The soft ablation of tissue by PIRL is achieved under the conditions of desorption by impulsive excitation (DIVE) [21] in which the water molecules contained within the tissue are transferred into the gas phase in an ultrafast, explosive manner. DIVE results in intact cellular biomolecules blasting out of the sample with minimized heating or shock wave damage imposed on the tissue and biomolecules [22] , [23] , [24] , [25] . Kwiatkowski et al showed that the tissue proteome is present in the condensate of the DIVE-induced tissue aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…The gentle process of PIRL ablation was confirmed by a study of Ren et al . in which they showed that protein conformations are not significantly disturbed and even large macromolecular structures such as viruses are extracted intact without losing their biological activity [107]. They further showed that biological samples can be taken down to the level of individual cells using PIRL offering a finer resolution than the finest biopsy needles, thus having the potential to enable minimally invasive biopsies.…”
Section: Ms-based Methods For Intraoperative Tumor Diagnosticsmentioning
confidence: 99%
“…At the same time, efficient energy redistribution into thermal modes is ensured by keeping the irradiance low enough to avoid nonlinear optical excitation of higher-lying molecular states. Picosecond infrared laser (PIRL) irradiation fulfilling these criteria has been shown to be well-suited for the extraction of large bio-molecules and even intact viruses for subsequent offline analysis, [20][21][22] as an atmospheric online ion source in combination with electrospray ionization (LAESI), 23 and has been suggested as a potential tool for sample-delivery in high-speed X-ray crystallography. 24 Moreover, the absence of ionizing radiation and minimal deposition of thermal and acoustic energy into the non-ablated sample surface make DIVE a valuable tool for precise material removal in surgical applications.…”
Section: Introductionmentioning
confidence: 99%